2023
DOI: 10.18280/ijsse.130215
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on Vulnerability Analysis of Phishing Attacks and Countermeasures

Ganga Abhirup Kothamasu,
Sree Keerthi Angara Venkata,
Yamini Pemmasani
et al.

Abstract: A great venue for communication amongst regular people is the internet. Many efficient communication methods are available online, such as email, mailing lists, discussion forums, chat services, online conferencing, and blogs. Social networking websites like Facebook, Instagram, and Twitter have recently entered the picture. People who want to steal personal information have discovered a technique with the least chance of getting detected without meeting the target, known as phishing. Phishing is a cybercrime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Phishing is a form of crime in the cyber world. One of the entrances for cybercriminals to commit phishing is through email, which sends messages that seem to come from trusted sources; victims are deceived and enter the spam web so that the personal information they have can be obtained by the perpetrator [8]. Previous research with business employee respondents identified effective email management practices as a key contributor to encouraging positive information security behaviors [17].…”
Section: Email Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Phishing is a form of crime in the cyber world. One of the entrances for cybercriminals to commit phishing is through email, which sends messages that seem to come from trusted sources; victims are deceived and enter the spam web so that the personal information they have can be obtained by the perpetrator [8]. Previous research with business employee respondents identified effective email management practices as a key contributor to encouraging positive information security behaviors [17].…”
Section: Email Managementmentioning
confidence: 99%
“…In general, cybercriminals directly attack end-users. Phishing is a cybercrime that uses texts, phone calls, and emails to obtain personal identities, banking information, credit card details, and passwords, by sending legitimate-looking emails or creating pop-up windows that appear to come from a trusted source to trick victims into providing their personal information to fake websites, and sometimes transferring malware to access victims' personal data [8]. Cybercriminals want to obtain credential information from users; this information is used to access the user's account so that the perpetrator can freely act as if they are the account owner.…”
Section: Introductionmentioning
confidence: 99%
“…If the attacker hacked the web application, they could access all the confidential or sensitive data available in the web application. It leads the attack to the next stage of an attack [3]. For example, if an online shopping website's credit or debit card details are saved, and the attackers hack the website, they can obtain the full card details and use them to steal money from the victim's account.…”
Section: Introductionmentioning
confidence: 99%